Can reproductive health services be used to screen for sexual and gender-based violence in post-conflict Northern Uganda? – a pilot study - Opiro, Keneth; Pebolo Pebalo, Francis; J Scolding, Neil; Hardy, Charlotte (African health sciences, 2024)
Background: Sexual and gender-based violence (SGBV), including rape and child sexual abuse, remains a significant challengein post-conflict northern Uganda. Many victims have never sought help. Consequently, the scale of the problem is not known,and SGBV victims’ injuries, both psychological and physical, remain hidden and unresolved. Objectives: We aimed to explore whether health workers in rural Reproductive Health Services (RHS), following specific training,could provide a valuable resource for SGBV screening and subsequent referral to targeted services. Methods: Our project had three elements. First, RHS workers were trained to use a questionnaire to screen subjects for pastSGBV. Second, the screening questionnaire was used by RHS workers over a 3-month period, and the data collected were analysedto explore whether the screening approach was an effective one in this setting, and to record the scale and nature of theproblem. Third, victims detected were offered referral as appropriate to hospital services or to a dedicated SGBV ActionAidshelter. Results: Of 1656 women screened, 778 (47%) had suffered SGBV: 123 rape, and 505 non-sexual violence. 1,254 (76%) had beendirectly or indirectly affected by conflict experiences; 1066 had lived in internally displaced persons camps. 145 (9%) requestedreferral to Gulu SGBV Shelter; 25 attended the shelter and received assistance, and 20 others received telephone counselling. Conclusion: Undetected SGBV remains a significant problem in post-conflict northern Uganda. RHS workers, following specifictraining, can effectively screen for and identify otherwise unrecognised survivors of SGBV. This matters because withoutongoing detection, survivors have no opportunity for resolution, healing or help. Keywords: SGBV; resource-poor setting; Screening.